Logistics and supply chain management: an area with a strategic service perspective - Crespo de Carvalho, J. (2014)
Logistics and supply chain management is an area that evolved deeply in the past years, integrating develop-ments of other areas of knowledge, both entrepreneurial and general. In this paper, a perspective of the evolu-tion of logistics and supply chain management is somehow designed. Traditionally, one may find logistics and supply chain management in friction with marketing and claiming for its own space. Nowadays, it seems difficult to see internal (logistics) versus external (marketing) wars and different orientations between marketing and logistics because they are both service and relations oriented. Simple transactions have been substituted, long time ago, for sustainable relations in the area of logistics and supply chain management. Finally, a more service oriented logic has been the footprint of logistics and supply chain management in current days and not, as pre-tended for some current rows of investigation, a simple transaction approach under a goods dominant logic. Lo-gistics and supply chain management is nowadays in parallel with an S-D logic (service dominant logic) because it is an area where relations matter, where sustainable links between networks of companies are crucial and where service is key in order to accommodate the contemporary thoughts and practices in the area. The main purpose of the paper is to stress the point that logistics and supply chain management is an area of service and value creation (or co-creation) and not a simple area of goods exchange and simple transactions.